Uji Daya Terima Produk Crackers Substitusi Tepung Cangkang Telur Ayam Ras (Gallus L.) sebagai Camilan Tinggi Kalsium - Niza Maizaroh; Dian Ayu Ainun Nafies (Lembaga Pengembangan Kinerja Dosen, 2026)
Crackers are snacks that are popular with various age groups, but generally have a relatively low calcium content so they do not contribute to meeting daily mineral needs. Therefore, food product innovations are needed to increase their nutritional value, one of which is by utilizing purebred chicken egg shells as a natural source of calcium. This study aims to analyze the effect of purebred chicken eggshell flour substitution on the acceptability of crackers and determine the best formulation as a high-calcium snack. The research method used an experimental design with a Complete Random Design (RAL) consisting of four treatments, namely P0 (100:0), P1 (90:10), P2 (85:15), and P3 (80:20). The testing is carried out qualitatively through organoleptic tests which include color, aroma, taste, and texture. The data was analyzed using the one-way ANOVA test and followed by the Post Hoc Kruskal-Wallis test if there were significant differences. The results showed that the best formulation was found in the P1 treatment with a 10% substitution of eggshell flour. Overall, the substitution of purebred chicken eggshell flour had no significant effect on the acceptability of crackers.